Brazil : Financial Sector Assessment Program-Technical Note on Supervision and Oversight of Financial Market Infrastructures. (IMF Staff Country Reports; Country Report ;, 2018)
Brazilian FMIs are among the top twenty worldwide. All together there are sixteen financial market infrastructures2 (FMIs) operating in the Brazilian payment system (SPB), out of which nine3 are systemically important and four belong to the top twenty FMIs in the world4. FMIs play an essential role in the Brazilian financial system and are highly relevant in terms of domestic financial stability. In terms of value of transactions, STR (Reserves Transfer System - Sistema de Transferencia de Reservas), the Brazilian Real Time Gross Settlement system (RTGS) is the backbone of the SPB, and belongs to the top ten large value payment systems worldwide. SELIC is among the top ten central securities depository/securities settlement systems (CSD/SSSs), CETIP among the top twenty SSSs, and BM and FBOVESPA Clearinghouse, the largest central counterparty (CCP) in Latin America, belongs to the top ten. These infrastructures facilitate the clearing, settlement, and recording of monetary and other financial transactions, such as payments, securities, and derivatives contracts (including derivatives contracts for commodities). Brazilian post-trading services are integrated. The entities providing securities settlement services also provide other post-trade processing, acting both as a clearing house, and a CSD or as a trade repository (TR).